Spectrophotometric Determination of Copper and Iron Reagents and Methods - Kumar Goswami, Ajay (De Gruyter, 2021)
The book covers specific and selective reagents for the determination of iron and copper by spectrophotometry. It provides methods for each group or class of reagents, including conditions, wavelength and interferences of other ions in samples. It is a unique guide for researchers in analytical chemistry from pharmaceutical to environmental monitoring laboratories working on iron and copper based products.